Gravity guide for modeling trade exports from Egypt to Mercosur countries (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses the use of gravity models to model trade exports from Egypt to Mercosur countries. Gravity models have been used to interpret exports from one country or economic bloc to another, taking into account factors such as GDP volume, population, exchange rates, distance, and the number of trade agreements. The article applies the Mercosur-Egypt gravity model to examine the impact of variables such as GDP per capita, population census, and Egypt's GDP on exports to the Mercosur group. The article uses a simple gravity model with the addition of population as an independent variable. The article presents the methodology and empirical results, including descriptive statistics for panel data and tests for panel data multicollinearity.